Effects of an inquiry-based science education training program on pre-service teachers. A mixed-methods case study. - García-Ruiz, Cristina; Lupión-Cobos, Teresa; Blanco-López, Ángel (Modestum, 2022)
The purpose of this research is to evaluate the impact of a one-semester training program on the teaching profile of five pre-service secondary science teachers, following a case study that allows us to focus closely on their perceptions related to inquiry-based science education (IBSE). Through a mixed-methods analysis of a variety of qualitative and quantitative research instruments, we aim to identify the changes in the pre-service teachers’ IBSE educational achievements in terms of their capability to effectively design inquiry activities, as well as in the perceptions affecting their teaching practice concerning emotions and self-efficacy. After a general overview of the results, we provide a specific vision for each participant, and present the conclusions regarding the acceptable level developed in both inquiry learning and teaching. Finally, we analyze the possible links between all the factors considered (perceptions, emotions, and design performance) and put forward several suggestions for professional development programs.
Keywords: Profesores de ciencias - Formación profesional; Ciencias - Estudio y enseñanza; Investigación activa en educación; Inquiry-based science education; Pre-service teacher training; Case study research